Police Pictures : The Photograph as Evidence. - Fogarty, Lori; Haworth-Booth, Mark; Phillips, Sandra S.; Squiers, Carol (San Francisco : San Francisco Museum of Modern Art, 1997)
Zealy, J.T. ; Fenton, Roger ; Galton, Sir Francis ; Duchenne, Guillaume Benjamin ; Bertillon, Alphonse ; Mason, D.D. Beatty & John T. ; Heller, L.H. ; Beato, Felice A. ; Gardner, Alexander ; Studio, Brady ; Butcher, Solomon D. ; Rils, Jacob ; Petouraud, Dr. ; Atget, Eugène ; Howard, Tom ; Fellig), Weegee (Arthur ; Gutmann, John ; Edgerton, Harold E. ; Mandel, Mike ; Sultan, Larry ; Burba, Harold ; Gatley, Dave ; Sochurek, Howard J. ; Garanger, Marc ; Ein, Nhem
Police Pictures : The Photograph as Evidence, San Francisco Museum of Modern Art, San Francisco, October 17, 1997 - January 20, 1998 ; Grey Art Gallery and Study Center at New York University, May 19 - July 18, 1998
Engels
boek